The Effectiveness of Complete Systematic Land Registration (PTSL) in Preventing Land Disputes - Augustine, Vieztanio Fynanda (Jurnal Konstatering, 2023)
This research aims to analyze: 1) The effectiveness of implementing Complete Systematic Land Registration (PTSL) in preventing land disputes. 2) Obstacles and solutions in the implementation of PTSL. The approach method used in this research is a sociological juridical approach. The specification of the research used is descriptive analytical research. This type of data uses primary data and secondary data obtained through interviews and literature study. The data analysis method used in this research is descriptive analysis. The research results concluded: 1). The effectiveness of the implementation of Complete Systematic Land Registration (PTSL) in preventing land disputes has been effective, although there are several obstacles in it. The effective implementation of the Complete Systematic Land Registration (PTSL) Program can be seen from the objectives to be achieved through the Complete Systematic Land Registration (PTSL) program. 2) Technical obstacles in implementing PTSL are the unavailability of parties from the relevant sub-districts, and in the field of measuring and mapping land plots which have not been thoroughly implemented. The solution is to carry out comprehensive measurements and mapping of land plots in the village/sub-district areas that have been designated as activity locations, both for registered land plots, improving the quality of registered land plots that have not been mapped, and unregistered land plots that carried out in a complete systematic manner grouped in one complete village/sub-district area.